DOCK2 Mutation and Recurrent Hemophagocytic Lymphohistiocytosis - Daniel D. Reiff; Mingce Zhang; Randy Q. Cron (Life, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a syndrome resulting from uncontrolled hyper-inflammation, excessive immune system activation, and elevated levels of inflammatory cytokines. HLH can be caused by the inability to downregulate activated macrophages by natural killer (NK) and CD8 cytotoxic T cells through a process reliant on perforin and granzyme B to initiate apoptosis. Homozygous genetic mutations in this process result in primary HLH (pHLH), a disorder that can lead to multi-system organ failure and death in infancy. Heterozygous, dominant-negative, or monoallelic hypomorphic mutations in these same genes can cause a similar syndrome in the presence of an immune trigger, leading to secondary HLH (sHLH). A genetic mutation in a potential novel HLH-associated gene, dedicator of cytokinesis 2 (DOCK2), was identified in a patient with recurrent episodes of sHLH and hyperinflammation in the setting of frequent central line infections. He required baseline immune suppression for the prevention of sHLH, with increased anti-cytokine therapies and corticosteroids in response to flares and infections. Using a foamy-virus approach, the patient’s DOCK2 mutation and wild-type (WT) control DOCK2 cDNA were separately transduced into a human NK-92 cell line. The NK-cell populations were stimulated with NK-sensitive K562 erythroleukemia target cells in vitro and degranulation and cytolysis were measured using CD107a expression and live/dead fixable cell dead reagent, respectively. Compared to WT, the patient’s DOCK2 mutation was found to cause significantly decreased NK cell function, degranulation, and cytotoxicity. This study speaks to the importance of DOCK2 and similar genes in the pathogenesis of sHLH, with implications for its diagnosis and treatment.